An explicit test of Pleistocene survival in peripheral versus nunatak refugia in two high mountain plant species. Issue 1 (12th December 2019) - Pan, Da; Hülber, Karl; Willner, Wolfgang; Schneeweiss, Gerald M.
Abstract: Pleistocene climate fluctuations had profound influence on the biogeographical history of many biota. As large areas in high mountain ranges were covered by glaciers, biota were forced either to peripheral refugia (and possibly beyond to lowland refugia) or to interior refugia (nunataks). However, nunatak survival remains controversial as it relies solely on correlative genetic evidence. Here, we test hypotheses of glacial survival using two high alpine plant species (the insect‐pollinated Pedicularis asplenifolia and wind‐pollinated Carex fuliginosa ) in the European Alps. Employing the iDDC (integrative Distributional, Demographic and Coalescent) approach, which couples species distribution modelling, spatial and temporal demographic simulation and Approximate Bayesian Computation, we explicitly test three hypotheses of glacial survival: (a) peripheral survival only, (b) nunatak survival only and (c) peripheral plus nunatak survival. In P. asplenifolia the peripheral plus nunatak survival hypothesis was supported by Bayes factors (BF> 100), whereas in C. fuliginosa the peripheral survival only hypothesis, although best supported, could not be unambiguously distinguished from the peripheral plus nunatak survival hypothesis (BF = 5.58). These results are consistent with current habitat preferences ( P. asplenifolia extends to higher elevations) and the potential for genetic swamping (i.e., replacement of local genotypes via hybridization with immigrating genotypes [expected to be higher in the wind‐pollinated C. fuliginosa ]). Although the persistence of plants on nunataks during glacial periods has been debated and studied over decades, this is one of the first studies to explicitly test the hypothesis instead of solely using correlative evidence.